Medically unexplained illness and the diagnosis of hysterical conversion reaction (HCR) in women’s medicine wards of Bangladeshi hospitals: a record review and qualitative study - Kendall, Emily A (BioMed Central, 2012)
BACKGROUND: Frequent reporting of cases of hysterical conversion reaction (HCR) among hospitalized female medical patients in Bangladesh’s public hospital system led us to explore the prevalence of “HCR” diagnoses within hospitals and the manner in which physicians identify, manage, and perceive patients whom they diagnose with HCR. METHODS: We reviewed admission records from women’s general medicine wards in two public hospitals to determine how often and at what point during hospitalization patients received diagnoses of HCR. We also interviewed 13 physicians about their practices and perceptions related to HCR. RESULTS: Of 2520 women admitted to the selected wards in 2008, 6% received diagnoses of HCR. HCR patients had wide-ranging symptoms including respiratory distress, headaches, chest pain, convulsions, and abdominal complaints. Most doctors diagnosed HCR in patients who had any medically-unexplained physical symptom. According to physician reports, women admitted to medical wards for HCR received brief diagnostic evaluations and initial treatment with short-acting tranquilizers or placebo agents. Some were referred to outpatient psychiatric treatment. Physicians reported that repeated admissions for HCR were common. Physicians noted various social factors associated with HCR, and they described failures of the current system to meet psychosocial needs of HCR patients. CONCLUSIONS: In these hospital settings, physicians assign HCR diagnoses frequently and based on vague criteria. We recommend providing education to increase general physicians’ awareness, skill, and comfort level when encountering somatization and other common psychiatric issues. Given limited diagnostic capacity for all patients, we raise concern that when HCR is used as a "wastebasket" diagnosis for unexplained symptoms, patients with treatable medical conditions may go unrecognized. We also advocate introducing non-physician hospital personnel to address psychosocial needs of HCR patients, assist with triage in a system where both medical inpatient beds and psychiatric services are scarce commodities, and help ensure appropriate follow up.